Development of a novel real-time polymerase chain reaction assay for the sensitive detection of Schistosoma japonicum in human stool. - Sara Halili; Jessica R Grant; Nils Pilotte; Catherine A Gordon; Steven A Williams (Public Library of Science (PLoS), 2021)
Background Elimination and control of Schistosoma japonicum, the most virulent of the schistosomiasis-causing blood flukes, requires the development of sensitive and specific diagnostic tools capable of providing an accurate measurement of the infection prevalence in endemic areas. Typically, detection of S. japonicum has occurred using the Kato-Katz technique, but this methodology, which requires skilled microscopists, has been shown to radically underestimate levels of infection. With the ever-improving capabilities of next-generation sequencing and bioinformatic analysis tools, identification of satellite sequences and other highly repetitive genomic elements for use as real-time PCR diagnostic targets is becoming increasingly common. Assays developed using these targets have the ability to improve the sensitivity and specificity of results for epidemiological studies that can in turn be used to inform mass drug administration and programmatic decision making. Methodology/principal findings Utilizing Tandem Repeat Analyzer (TAREAN) and RepeatExplorer2, a cluster-based analysis of the S. japonicum genome was performed and a tandemly arranged genomic repeat, which we named SjTR1 (Schistosoma japonicum Tandem Repeat 1), was selected as the target for a real-time PCR diagnostic assay. Based on these analyses, a primer/probe set was designed and the assay was optimized. The resulting real-time PCR test was shown to reliably detect as little as 200 ag of S. japonicum genomic DNA and as little as 1 egg per gram of human stool. Based on these results, the index assay reported in this manuscript is more sensitive than previously published real-time PCR assays for the detection of S. japonicum. Conclusions/significance The extremely sensitive and specific diagnostic assay described in this manuscript will facilitate the accurate detection of S. japonicum, particularly in regions with low levels of endemicity. This assay will be useful in providing data to inform programmatic decision makers, aiding disease control and elimination efforts.